Reading for understanding how reading apprenticeship improves disciplinary learning in secondary and college classrooms - Greenleaf, Cynthia; Schoenbach, Ruth; Friedrich, Linda; Murphy, Lynn 1945-; Hogan, Nika (Hoboken, NJ Jossey-Bass, 2023)
Low levels of adolescent literacy are considered the major contributor to the nation's school dropout crisis. Each year some 1.2 million high school students fail to graduate with their peers. The problem is equally acute in community colleges, where high proportions of incoming freshmen how require courses in remedial reading. While elementary schools have, on average, improved student achievement in the past decade, middle level students' overall scores have been flat and high school students' scores have decreased. This downward curve can largely be traced to deficits in reading performance beyond the elementary grades. The National Assessment of Educational Progress (NAEP) shows that 8th grade reading scores have remained the same and 12th grade scores have dropped significantly since 1992. Reading for Understanding is a valuable resource in the effort to remedy this growing issue"--
Includes index.
Principal author for the previous edition is Ruth Schoenbach.
Keywords: Reading (Higher education) -- United States; Reading (Secondary) -- United States